Monocanalicular repair using angiocatheter tube as a stent in a young patient in a rural setup - Tathe, S; Dhaytadak, P (Nepalese Journal of Ophthalmology, 2013)
Introduction: Ocular injuries commonly involve the lacrimal system. Case: A 14-year-old male had an eyelid injury with a canalicular tear. An angiocatheter tube was used as a stent for canalicular reconstruction. The focus of this report is on the method used, as well as the material for the repair in a rural hospital. Conclusion: Angiocatheter tube can be a suitable alternative to silicone tube for canalicular repair. Nepal J Ophthalmol 2013; 5(9):106-108 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7835